Aberrant Dynamic Functional Connectivity of Posterior Cingulate Cortex Subregions in Major Depressive Disorder With Suicidal Ideation - Li, Weicheng; Wang, Chengyu; Lan, Xiaofeng; Fu, Ling; Zhang, Fan; Ye, Yanxiang; Liu, Haiyan; Wu, Kai; Lao, Guohui; Chen, Jun; Li, Guixiang; Zhou, Yanling; et al. (Frontiers in Neuroscience, 2022)
Accumulating evidence indicates the presence of structural and functional abnormalities of the posterior cingulate cortex (PCC) in patients with major depressive disorder (MDD) with suicidal ideation (SI). Nevertheless, the subregional-level dynamic functional connectivity (dFC) of the PCC has not been investigated in MDD with SI. We therefore sought to investigate the presence of aberrant dFC variability in PCC subregions in patients with MDD with SI. We analyzed resting-state functional magnetic resonance imaging data from 31 unmedicated patients with MDD with SI (SI group), 56 unmedicated MDD patients without SI (NSI group), and 48 matched healthy control subjects. The sliding-window method was applied to characterize the whole-brain dFC of each PCC subregion (the ventral PCC [vPCC] and dorsal PCC [dPCC]). In addition, we evaluated associations between clinical variables and the aberrant dFC variability of those brain regions showing significant between-group differences. Compared with healthy controls, the SI and NSI groups exhibited higher dFC variability between the left dPCC and left fusiform gyrus, and between the right vPCC and left inferior frontal gyrus. The SI group showed higher dFC variability between the left vPCC and left inferior frontal gyrus than the NSI group. Furthermore, the dFC variability between the left vPCC and left inferior frontal gyrus was positively correlated with SSI score in patients with MDD (i.e., the SI and NSI groups). Our results indicate that aberrant dFC variability between the vPCC and inferior frontal gyrus might provide a neural-network explanation for SI, and may provide a potential target for future therapeutic interventions in patients with MDD with SI.